ANALYSIS OF DIFFERENTIATION STRATEGIES IN MAINTAINING CUSTOMER LOYALTY IN FOOD MSMES IN JEMBER (CASE STUDY OF GADO-GADO BAROKAH CAK KIRUN) - Juariyah, Siti; Santoso, Budi (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to find out the strategy of maintaining customer loyalty in culinary businesses. One of the businesses that supports the national economy that cannot be underestimated is Micro, Small, and Medium Enterprises (MSMEs), namely Gado-Gado Cak Kirun. Method: This research uses descriptive qualitative methods through the collection of survey data and observation. Results: The research findings indicate that Gado-Gado Cak Kirun has a distinctive aroma of peanut sauce that is savory, sweet, and spicy, with a fresh texture similar to a salad with peanut sauce, full of a variety of vegetables and combined with quality protein sources, carbohydrate sources, and sources of fat from peanuts, making one serving nutritionally complete. Marketing is conducted using social media accounts, and the key attitudes applied in serving consumers include manners, friendliness, and patience. Novelty: This study highlights the combination of product uniqueness, digital marketing strategies, and customer service approaches in maintaining customer loyalty in the culinary business, specifically within MSMEs.